Blowfish - Cho, Kyŏng-nan, 1969- (Astra House, 2025)
"For readers of Han Kang and Sheila Heti, an atmospheric, melancholic novel about a successful sculptor who decides to commit suicide by artfully preparing and deliberately eating a lethal dish of blowfish"--